PENDIDIKAN REMAJA DALAM KELUARGA DI DESA MERABUAN, KALIMANTAN BARAT (PERSPEKTIF PENDIDIKAN AGAMA ISLAM) - Aslan, Aslan (Pascasarjana UIN ANTASARI Banjarmasin, 2017)
The research discusses adolescents as an issue of education in the family. As many experts recognize that family education is a major issue in the study of Islamic education. This is because the family is the first place for learning and planting Islamic values of a child to adolescence. In the context of family education, parents have a very vital position, in which parents become the main figures for a child in obtaining the internalization of the expected values in the family. This study is a field research that takes the site to families in Merabuan village, Sambas district, West Kalimantan, focusing on adolescents as the unit of analysis. Data collection techniques in this research using interviews, observation, and documentation. The findings of this research explain that family education conducted by families in Merabuan village through exemplary in the family environment, with the ways often provide guidance and advice, encouraging adolescents into youth members of the mosque, including adolescents praying in congregation in the mosque.